The phenomenology of the first panic attack in clinical and community-based samples - Pané-Farré, Christiane A.; Stender, Jan P.; Fenske, Kristin; Deckert, Jürgen; Reif, Andreas; John, Ulrich; Schmidt, Carsten Oliver; Schulz, Andrea; Lang, Thomas; Alpers, Georg W.; Kircher, Tilo; Vossbeck-Elsebusch, Anna N.; et al. (Journal of anxiety disorders, 2014)
•Symptoms, circumstances, and consequences of first panic attacks were assessed.•We compared first panic attacks of panic disorder with vs. without agoraphobia.•Attacks leading to PD with agoraphobia were more severe and occurred in public.•We also contrasted first attacks leading to PD vs. first isolated panic attacks.•Attacks leading to PD were more severe than first isolated attacks. The purpose of the study was to contrast first panic attacks (PAs) of patients with panic disorder (PD) with vs. without agoraphobia and to explore differences between first PAs leading to the development of PD and those that remain isolated. Data were drawn from a community survey (N=2259 including 88 isolated PAs and 75 PD cases). An additional sample of 234 PD patients was recruited in a clinical setting. A standardized interview assessed the symptoms of the first PA, context of its occurrence and subsequent coping attempts. Persons who developed PD reported more severe first PAs, more medical service utilization and exposure-limiting coping attempts than those with isolated PAs. The context of the first PA did not differ between PD and isolated PAs. PD with agoraphobia was specifically associated with greater symptom severity and occurrence of first attacks in public. Future research should validate these findings using a longitudinal approach.